Nutritional studies in kinnow (Indian Journal of Arid Horticulture, 2025)
The study on "Nutritional studies conducted in Kinnow "at Agriculture Research Station, Sri Ganganagar during 1993- 1997 revealed that the nitrogen doses at 60g, 120g, 180g, 300g and 500g from 1st, 2nd, 3rd, 4th and 5th year, respectively in three split doses in February, April and August-September gave significantly better effect on the growth parameters viz., plant height, plant spread, root stock and scion growth and quality parameters of Kinnow fruit as compared to state recommendation.
Keywords: Growth parameters; nitrogen levels, nutritional